Das Gewissen - Schaede, Stephan; Moos, Thorsten (Mohr Siebeck, 2015)
The concept and phenomenon of conscience are the subject of an inter-disciplinary exploration in this collection. With contributions from the fields of theology, law, philosophy, and many more, those interested in the concept of conscience will be able to follow a course of inquiry which informs on controversial perspectives, uncovers explanatory expectations on each of the other disciplines and crystallizes inter-disciplinary concurrence.